Stress and strain analysis of buried PE pipelines subjected to mechanical excavation. (December 2019) - Wu, Kai; Zhang, Hong; Liu, Xiaoben; Bolati, Dinaer; Liu, Gaoling; Chen, Pengchao; Zhao, Yatong
Abstract: With the rapidly development of urbanization progress, various pavement constructions tend to be the primary threat to the structural integrity of buried pressurized polythene material pipes. Moreover, the excavation damage of the third-party interference is the main cause of buried pipe's failure. Thus, in the presented study, a validated finite element model was established to characterize the failure behavior of buried PE80 pipes under excavation by the hydraulic excavators, influence of various factors, such as the pipe diameter, pipe thickness, internal pressure, tooth size, excavation position, on pipeline failure behavior were elaborated in detail. Results show that the excavation load could induce large plastic deformation on PE pipes, which suggested that strain-based criterion is more suitable comparing with the stress based criterion for the failure assessment of PE pipes. It also indicated that the excavation load generally give rise to certain strain in the contact area between pipes and bucket teeth, which locates exactly at two sides of the end of the contact area. Besides, relative small deformation would also be induced on both sides of pipes. Results indicate that the increase of internal pressure could enhance the ability of pipes to resist the excavation load. Pipe thickness had a significant effect on the critical resistance, the increase of pipe thickness can dramatically improve the ability of pipeline to resist deformation. Decreasing the pipe diameter or increasing tooth length, tooth width can also effectively increase pipe's critical resistance. As for the excavate position, the simulation revealed that the critical load reached the minimum value when the excavate angle was 30° or the excavation offset distance was 0.3 D . In addition, a prediction equation for the critical pipe resistance force of PE80 pipelines under the excavate load was derived based on numerical results and regression analysis. Good agreement was achieved between the proposed method and the numerical results. Highlights: Refined three dimensional elastoplastic FE simulations for buried PE pipes under excavation load were performed. The feasibility of stress-based failure criterion and strain based failure criterion for PE pipes was derived. Influences of pipe diameter, wall thickness, tooth size, excavation position on PE pipes' failure mechanism were discussed. A prediction formula of the pipe resistance of buried PE80 pipes under excavation load was proposed.